2013
DOI: 10.1016/j.ast.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary design optimization of blended-wing-body transport aircraft with distributed propulsion

Abstract: 2016-12-24T18:18:19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 26 publications
0
35
0
2
Order By: Relevance
“…The distributed propulsion is a revolutionary technology that seeks to reduce the noise and weight of an aircraft by means of replacing large propulsors with a moderate amount of small ones along the airframe [16] as depicted in Figure 1. This offers the possibility of increasing the propulsive efficiency because a larger propulsive area is considered, which in turn, implies a lower jet velocity.…”
Section: Uav Design Methodology 21 Distributed Electric Propulsionmentioning
confidence: 99%
See 1 more Smart Citation
“…The distributed propulsion is a revolutionary technology that seeks to reduce the noise and weight of an aircraft by means of replacing large propulsors with a moderate amount of small ones along the airframe [16] as depicted in Figure 1. This offers the possibility of increasing the propulsive efficiency because a larger propulsive area is considered, which in turn, implies a lower jet velocity.…”
Section: Uav Design Methodology 21 Distributed Electric Propulsionmentioning
confidence: 99%
“…This baseline configuration has been selected based on previous research [11], where it has been found that BWB configurations offer high volumetric efficiency while providing good aerodynamic performance [12] as a result of the elliptical lift distribution improvement over the whole airframe [13][14][15]. Furthermore, the BWB model facilitates the integration of different propulsion architectures, which results in a broader spectrum of configurations for distributed propulsion [16].…”
Section: Introductionmentioning
confidence: 99%
“…In this case the main engines weight has been modelled with the approach developed in ref. 16 , which enables to scale the weight of the engine based on the sea level thrust. The simple equation 7 enabled to quantitatively establish the difference between smaller and larger engines, which is good enough for the weight analysis used in this study.…”
Section: Weight Modellingmentioning
confidence: 99%
“…The 2014 final report demonstrated that hybrid SUGAR Volt could meet the NASA goals regarding fuel burn [10]. Several academic studies [11,12] demonstrated that distributed propulsion could provide substantial performance benefits to blended-wing-body transport aircraft.…”
Section: Introductionmentioning
confidence: 99%